Lithuanian Proverbs as a Source of Natural Law Regulations in the Historical Writings of Simonas Daukantas - Pivoras, Saulius (Tautosakos darbai, 2024)
The purpose of this article is to argue that Simonas Daukantas used the material of Lithuanian folklore, mainly proverbs, as a historical source in his works on the history of Lithuania, and analyze his reasons for doing that. Daukantas used the Lithuanian proverbs as a source for studying socio-moral and legal attitudes, and elucidating their role in the process of history. He was most interested in identification and clarification of Lithuanian customary law norms and natural principles, relying on proverbs. Folklore data was instrumental for Daukantas in proving that the social order in ancient Lithuanian history was based on natural law, and there were natural regulations that fostered the natural human freedom and industriousness.